Pembelajaran Pendidikan Agama Islam di Sekolah Dasar Luar Biasa (SDLB) C Kemala Bhayangkari 2 Gresik - Ulfa, Mariya (Universitas Nahdlatul Ulama Pasuruan, 2021)
This study was conducted to determine the learning of Islamic Religious Education which was carried out at the Extraordinary Elementary School (SDLB) C Kemala Bhayangkari 2 Gresik. This study uses a qualitative approach with descriptive analytical research type. Collecting data using the method of observation, interviews and documentation. As a school with students with special needs (ABK) status, it is certainly not easy to carry out every learning activity. Especially in Islamic Religious Education which is oriented to the practice of religious teachings in everyday life. There needs to be good preparation before carrying out learning activities so that the evaluation obtained is in line with expectations. From the results of the study, it is known that there are 3 processes carried out by the Extraordinary Elementary School (SDLB) C Kemala Bhayangkari 2 Gresik in the implementation of Islamic Religious Education learning, namely: preparation, implementation and evaluation. The implementation of learning is carried out in the form of formal education in the subjects of Islamic Religious Education and non-formal education including Islamic Literacy, Dhuhur Prayer in congregation and Scout Extracurricular